A competência legislativa suplementar do município na Constituição Federal de 1988 - Cruz, Gabriela Moccia de Oliveira (2012)
The focus of this study is the supplemental legislative competence of the municipalities, specifically. The municipal jurisdiction has two foci of activity: the matters of exclusive competence and matters of concurrent jurisdiction, ie, those that are shared by the local entity with the Union and the States. For the exercise of the concurrent jurisdiction, the Federal Constitution provides in article 24, a rule: the general norms are edited by the Union and are supplemented by the States and Federal District. Although article 24 did not mention the municipalities, the entity was awarded by the supplemental legislative competence in the article 30, II, which gives it permission to complement Federal and State laws as appropriate . We follow analyzing the interpretations offered by the Brazilian courts and the specialized doctrine. Settled this discussion, we depart for the analysis of four cases: the straw burning of sugar cane, the free distribution of plastic bags in the supermarkets, the entry of people wearing helmets in public places or open to the public, and accessibility at commercial establishments. Despite the usual centralization of decisions in the framework of the Union, which depreciates municipal activity in the analyzed cases, we identified a trend of reorientation of this interpretation by the Brazilian courts and doctrine that confirms what we defend: a stronger role of the municipality in the Federation, because it is the closest political entity of the society